Reactivation of Internet Memes of the Military Era: Psycholinguistic Markers - Дмитро Сизонов; Ольга Злотник-Шагіна (Психолінгвістика)
Purpose. The purpose of the article is to clarify the communicative possibilities and stylistic functions of Internet memes as verbalized representatives of the military period (2022-...) and carriers “collaborative memory” (Conte, Padulo, & Fairfield, 2024) in virtual communication, which is based on socio- and psycholinguistic dimensions. The dynamics of functioning of the memes in the information space of Ukraine is explained, according to the authors, by the rapid development of this media genre, an instant associative reflection on the current events of the present, and the precedence of the expression that is embedded in an Internet meme.